2010
DOI: 10.1213/ane.0b013e3181e368d2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Attenuates Pulmonary Dysfunction After Unilateral Thigh Tourniquet–Induced Ischemia–Reperfusion

Abstract: Pulmonary gas exchange is impaired after lower limb ischemia-reperfusion associated with the clinical use of a tourniquet for lower limb surgery. Ischemic preconditioning preceding tourniquet-induced ischemia attenuates lipid peroxidation and systemic inflammatory response and mitigates pulmonary dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 31 publications
2
51
0
2
Order By: Relevance
“…The basic mechanism of remote IP is preparing one organ for ischemic insult by the application of IP to another site of the body (generally a lower limb) (1618). Limb IP decreases the IR injuries in the lung, liver, myocardium and kidney and ameliorates the hemodynamic response to tourniquet application (1927). These previous studies have shown that limb IP is a promising method for the prevention of IR-induced tissue injuries in certain clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The basic mechanism of remote IP is preparing one organ for ischemic insult by the application of IP to another site of the body (generally a lower limb) (1618). Limb IP decreases the IR injuries in the lung, liver, myocardium and kidney and ameliorates the hemodynamic response to tourniquet application (1927). These previous studies have shown that limb IP is a promising method for the prevention of IR-induced tissue injuries in certain clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One study used both anaesthetic and antioxidant intervention (propofol and N‐acetyl‐cysteine) (Table ). Three studies used ischaemic pre‐conditioning (Table ) and one study used both ischaemic pre‐conditioning and antioxidant intervention (N‐acetyl‐cysteine) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory mediators, such as interleukin-6, tumor necrosis factor, intracellular adhesion molecule, matrix metalloproteinase 9, and C-reactive protein, have been linked to DCI and are downregulated through preconditioning. [40][41][42][43][48][49][50][51][52][53][54] In addition, tissue is rendered more tolerant to ischemia through reduction of excitotoxicity and metabolic protection by enhancing mitochondrial function. Preconditioning also affects several other pathways that have been implicated in vasospasm and DCI.…”
Section: Preconditioning To Ameliorate Vasospasm and DCImentioning
confidence: 99%